Methods of wintering steer calves that are to be grazed a full season and sold off grass. - Smith, E.F.; Cox, R.F.; Good, D.L. (Kansas Agricultural Experiment Station, 2012)
The primary objective of this test was to find the most satisfactory method or methods of wintering steer calves that are going to be grazed on bluestem pasture during the summer and sold off grass as feeder yearlings. This is the second in a series of three tests. The third test is now under way and the wintering phase is reported in this publication.
Keywords: Beef; Yearlings; Bluestem pasture; Wintering phase